Lessons from unsuccessful energy and buildings sustainability actions in university campus operations - Amaral, Ana Rita (2021)
Higher Education Institutions (HEIs) are increasingly striving to deploy actions that promote the efficient use of energy and other resources on university campuses. Successful sustainability initiatives are vastly described in literature, especially for the operations phase. In turn, reports on unsuccessful cases are small in number, or are overlooked and undiscussed, possibly providing a biased view of reality, thus hiding eventual failures. The main objective of this article is to highlight those latter cases and discuss the causes of such results. Through a systematic review of empirical-based scientific literature on ineffective or less successful sustainability actions in the areas of ‘Energy’ and ‘Buildings’ on campus operations, it was possible to identify common potential triggering factors for the unsuccess. These were classified into four groups according to the number of occurrences in literature: technical, economic, climatic and behavioral. Within these groups, the main causes include: inadequate planning, the inappropriate design of systems, the lack of proper maintenance, the low return on investment, mismatch between the actions and the local climate, or the uncertainty of long-term commitment to a sustainable behavior. Based on these findings, a set of lessons were disclosed for each group, which may be helpful for all those who are involved in decision-making, planning or monitoring of sustainability actions on campus, as a means to help anticipate and overcome difficulties in early phases. Lastly, more empirically based literature is encouraged, as the disproportion between information on the description of actions and on their impacts is notorious.